Globe trekker. Puerto Rico [videorecording (DVD)] - Harding, Zay (Pilot Productions, 2012)
Roving Globe Trekker host Zay Harding ventures to the heart of the Caribbean and discovers sun-kissed beaches, dramatic mountains, a rich colonial history, and great music. Join Zay on an incredible adventure to Puerto Rico, the 'island of enchantment'.